Arborização viária urbana e o seu potencial turístico na cidade de Maringá/PR - Barros, Rafaela De Angelis (2010)
This present study aims to Know the influence of the city road afforestation compounding the urban infrastructure, as a touristic attraction factor. As a mean to this development, the city of Maringa/PR was chosen by its attributes such as the streets afforestation, associated to the fact that this city is a "corridor" for many crossing tourists going to Foz do Iguaçu, Argentina and Paraguay. The theoretic/methodological referential is based on a field and exploratory research, proposing to investigate the reality about a complex activity of this "green" potential. The inclusion about the touristic potential of the road trees was done through a questionnaire with 450 tourists hosted in the four biggest hotels in Maringa downtown. The structure and semi structured questions allowed to identify the social economic profile of the participants, as well as to obtain quantitative and qualitative data about their perception of road trees from Maringa. Through the interviews it was noticed that, for 90% of the interviewed tourists, the road afforestation in Maringa might be considered one tourist attraction of the city. From this significant percentage, it is recommended public policy establishment which can cooperate with the tourism increment in Maringa.